2019
DOI: 10.1210/en.2019-00258
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ Mediates Mineralocorticoid Receptor Activation by Angiotensin II to Modulate Smooth Muscle Cell Function

Abstract: Angiotensin II (AngII) and the mineralocorticoid receptor (MR) ligand aldosterone both contribute to cardiovascular disorders, including hypertension and adverse vascular remodeling. We previously demonstrated that AngII activates MR-mediated gene transcription in human vascular smooth muscle cells (SMCs), yet the mechanism and the impact on SMC function are unknown. Using an MR-responsive element-driven transcriptional reporter assay, we confirm that AngII induces MR transcriptional activity in vascular SMCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Wnt5a is involved in the development of various diseases such as atherosclerosis, cancer, and inflammation [24][25][26] and plays a critical role in numerous cellular processes from embryonic morphogenesis to postnatal development [5]. Our previous study has illustrated that the combination of Wnt5a and Ror2 together suppresses the expression of adenosine triphosphate-binding cassette transporter A1 (ABCA1) promotes cholesterol accumulation and secretion of pro-inflammatory cytokines and nuclear translocation of NF-κB in VSMCs, and ultimately leads to atherosclerosis [16]. OxLDL increased Wnt5a expression, induced foam cell formation, and affected the migration and phenotype of VSMCs [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt5a is involved in the development of various diseases such as atherosclerosis, cancer, and inflammation [24][25][26] and plays a critical role in numerous cellular processes from embryonic morphogenesis to postnatal development [5]. Our previous study has illustrated that the combination of Wnt5a and Ror2 together suppresses the expression of adenosine triphosphate-binding cassette transporter A1 (ABCA1) promotes cholesterol accumulation and secretion of pro-inflammatory cytokines and nuclear translocation of NF-κB in VSMCs, and ultimately leads to atherosclerosis [16]. OxLDL increased Wnt5a expression, induced foam cell formation, and affected the migration and phenotype of VSMCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…The Protein kinase C (PKC) family of serine/threonine kinases is evolutionarily conserved and expressed in a wide variety of species [15]. Emerging evidence has shown that PKC is involved in the proliferation of VSMCs [16]. Interestingly, Ror2 activation by a noncanonical Wnt ligand can activate PKC and c-Jun N-terminal kinases (JNK) and promote N-methyl-d-aspartic acid (NMDA) receptor synaptic responses [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also important to highlight that macrophages do not express 11β-hydroxysteroid dehydrogenase type 2, the enzyme that inactivates glucocorticoids and provides specificity to mineralocorticoid actions. Therefore, MR activation in macrophages is likely to be mediated instead by glucocorticoids ( Rickard et al, 2009 ; Usher et al, 2010 ), although direct MR activation by Ang II has been described ( Lu et al, 2019 ). Despite these limitations of the MyMRKO model, our findings support a critical role for myeloid cells, in particular macrophages, as potential mediators of vascular injury resulting from inappropriate MR activation.…”
Section: Discussionmentioning
confidence: 99%
“…For PKCδ, angiotensin II led to MR-PKCδ complex formation in association with increased serine phosphorylation of the MR-NTD in vascular cells. AngII also activated MR transcriptional activity, target gene expression, and SMC proliferation in a PKCδ-dependent manner that may involve phosphorylation of MR-NTD (Lu et al, 2019). Although MR phosphorylation by PKC isoforms has been demonstrated by several groups, it is not always clear if the effects described evolve from a direct MR phosphorylation or indirectly through phosphorylation of co-regulators or a combination of both.…”
Section: Posttranslational Modifications Of the Mineralocorticoid Receptor Phosphorylationmentioning
confidence: 99%